Balancing Civil and Political Rights: Constitutional Court Powers in Indonesia and Austria - Razak, Askari; Muhtar, Mohamad Hidayat; Rivera, Kevin M.; Saragih, Geofani Milthree (Journal of Indonesian Legal Studies, 2023)
This study focuses on analyzing the role and challenges faced by the Constitutional Court in upholding political and civil rights in Indonesia and Austria. This research explores various conceptual and comparative aspects of law through normative research methods and delves deeper into how these institutions operate in practice. Analysis shows that the Constitutional Courts in both countries serve as the primary guardians of justice and human rights. However, it must also operate in a complex environment, dealing with social, political, and international challenges. The study found that changes in laws and regulations have significant potential to strengthen the authority and effectiveness of the Constitutional Court. This is reflected in the constitutional evolution in both countries, where legal and regulatory reforms have played an important role in shaping and defining the authority of the Constitutional Court. This study confirms the importance of increasing the capacity and legal knowledge of members of the Constitutional Court, as well as the need for greater understanding and appreciation from the public of this institution's vital role and function. This research contributes to understanding how constitutional institutions can adapt and evolve to meet challenges in enforcing political and civil rights.